Developing a Tax Audit Model with an Emphasis on Organizational Tax Compliance - Kiasati, Mohammad; Ghanbari, Mehrdad; Mohammadi Yarijani, Foroozan; Nooraie, Maryam (Business, Marketing, and Finance Open, 2027)
The present study was conducted with the aim of developing a tax audit model with an emphasis on organizational tax compliance. This study was interpretive, applied, qualitative, field-library based, and grounded theory research employing Glaser’s emergent approach. The participants in this study consisted of 19 university professors, specialists, experts, and practitioners who had research or executive experience in the field of tax auditing or were members of the official tax consultants’ association. They were selected through snowball sampling until theoretical saturation of the research constructs was achieved. Data were collected using semi-structured interviews. Data analysis in the present study was conducted in two stages. In the first stage, the demographic characteristics of the participants were examined. In the second stage, based on the Glaserian grounded theory approach, the findings were analyzed through open, axial, and selective coding using MAXQDA software. The results indicated that the tax audit model with an emphasis on organizational tax compliance consisted of three dimensions: influencing factors, strategies, and consequences. The influencing factors included six categories: level of trust, organizational factors, legal factors, level of transparency, cultural factors, and level of expertise and capability. The strategies included four categories: educational solutions, executive solutions, adjustment mechanisms, and communication strategies. The consequences included three categories: consequences related to taxpayers, consequences related to the tax organization, and consequences related to the country’s macro-level issues. Therefore, managers of the country’s tax auditing system can, in addition to paying attention to the factors affecting tax auditing and tax compliance, implement the strategies identified in the present study in order to ultimately provide the basis for positive outcomes for taxpayers, the tax organization, and the country’s broader macroeconomic issues.